2015
DOI: 10.1111/hpb.12331
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant stereotactic body radiotherapy following transarterial chemoembolization in patients with non‐resectable hepatocellular carcinoma tumours of ≥3 cm

Abstract: This retrospective study suggests that in patients with HCC tumours of ≥ 3 cm, treatment with TACE + SBRT provides a survival advantage over treatment with only TACE. Confirmation of this observation requires that the concept be tested in a prospective, randomized clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 32 publications
0
68
1
Order By: Relevance
“…Both studies found that the addition of SBRT resulted in improved local control with no increase in high-grade toxicity. Furthermore, in tumours ≥3cm, after censoring for liver transplantation, overall survival was significantly better with TACE plus SBRT compared to TACE alone (median survival 33 and 20 months respectively; p=0.02) 32 . There was no overall survival advantage from the combination in tumours ≤3cm, although disease free survival (DFS) was significantly better with the addition of SBRT in treatment naïve patients (1-year DFS 71.4% and 24.8% respectively, p=0.029) 33 .…”
Section: Clinical Evidence: Prospective Datamentioning
confidence: 95%
See 2 more Smart Citations
“…Both studies found that the addition of SBRT resulted in improved local control with no increase in high-grade toxicity. Furthermore, in tumours ≥3cm, after censoring for liver transplantation, overall survival was significantly better with TACE plus SBRT compared to TACE alone (median survival 33 and 20 months respectively; p=0.02) 32 . There was no overall survival advantage from the combination in tumours ≤3cm, although disease free survival (DFS) was significantly better with the addition of SBRT in treatment naïve patients (1-year DFS 71.4% and 24.8% respectively, p=0.029) 33 .…”
Section: Clinical Evidence: Prospective Datamentioning
confidence: 95%
“…Normal liver doses and the severity of cirrhosis are important in predicting hepatic toxicity 15,16,[25][26][27] . Classic and non-classic radiation-induced liver disease (RILD) have been described 28 SBRT and TACE to TACE alone in tumours ≥3cm and ≤3cm respectively in retrospective series 32,33 . Both studies found that the addition of SBRT resulted in improved local control with no increase in high-grade toxicity.…”
Section: Clinical Evidence: Prospective Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It can be a treatment for HCC with >3 cm tumour size. 159 In a retrospective study the effect of the combination of TACE + 3-DCRT + HIFU was evaluated. After the combination of TACE and 3-DCRT, HIFU was administered.…”
Section: Chemotherapy and Radiotherapymentioning
confidence: 99%
“…SBRT can be a complementary treatment to TACE, since the ischemic effects of TACE are less potent in the surrounding well-oxygenated periphery of the HCC tumor where radiation is the most effective. A retrospective study suggests a survival advantage in large tumors for the combination of SBRT and TACE as compared to TACE alone [52] . Due to the limited data regarding SBRT, it is considered under investigation, and not yet recommended by the EASL guidelines as part of the HCC therapy regimen.…”
Section: Stereotactic Body Radiotherapymentioning
confidence: 99%